Uphill racewalking at iso-efficiency speed - Padulo, J.; Annino, G.; Tihanyi, J.; Calcagno, G.; Vando, S.; Smith, L.; Vernillo, G.; La Torre, A.; D'Ottavio, S. (The Journal of Strength and Conditioning Research, 2013)
The aim of this study was to investigate the effects of gradients (0, 2, and 7%) on biomechanical parameters during racewalking (RW) at iso-efficiency speed (IES). During the experiment, 12 high-level athletes performed at IES on different slopes. The parameters studied were surface muscular activity (EMG) of 5 muscles of the leg using Muscle Lab (Boscosystem); kinematic parameters were collected using a high-speed camera (210 Hz) analyzed with Dartfish 5.5Pro; and heart rate (HR) was monitored with a Cardio Polar. The results showed step length (SL), step frequency (SF), and internal work (WINT) decreased with increased treadmill gradient: SL = ([0-2% = 3.48%, p = 0.158], [0-7% = 12.17%, p < 0.001]); SF = ([0-2% = 2.38%, p = 0.173], [0-7% = 6.07%, p < 0.01]); WINT = ([0-2% = 8.34%, p < 0.001], [0-7% = 22.81%, p < 0.0001]). Conversely, contact time (CT) and HR increased less significantly with the increased gradients: CT = ([0-2% = 2.46%, p = 0.198], [0-7% = 6.56%, p < 0.01]); HR = ([0-2% = 0.62%, p = 0.652], [0-7% = 3.25%, p < 0.05]). The knee angle (KE) increased, whereas ankle angle (AK) and hip angle (HP) decreased with the increased gradients: AK = ([0-2% = 1.69%, p < 0.001], [0-7% = 1.13%, p < 0.01]); HP = ([0-2% = 0.22%, p < 0.03], [0-7% = 0.16%, p = 0.456]); KE = ([0-2% = 1.01%, p < 0.001], [0-7% = 1.60%, p < 0.001]). Electromyography (EMG) significantly decreased with the increased gradients in the: tibialis anterior ([0-2% = 22.49%, p < 0.0001], [0-7% = 41.18%, p < 0.0001]) and rectus femoris ([0-2% = 15.35%, p < 0.0001], [0-7% = 29.13%, p< 0.0001]). In contrast, EMG activity was significantly increased in the vastus lateralis ([0-2% = 22.95%, p < 0.0001], [0-7% = 31.15%, p < 0.0001]), gastrocnemius medialis ([0-2% = 21.40%, p < 0.001], [0-7% = 48.37%, p < 0.0001]), and biceps femoris ([0-2% = 190.78%, p < 0.0001], [0-7% = 201.37%, p < 0.0001]). The results indicate that increasing the gradient to 2% did not elicit an increased HR in racewalkers; however, at a 7% gradient, greater muscle activity was required.